Multiple family SES indices: Variations between middle class and lower social class undergraduate samples - Reyes, Melissa Lopez (Animo Repository, 2016)
In the face of socioeconomic hardships, social work programs for youth have been targeting not only the lower social class but also the middle class. To address the need for socioeconomic status (SES) screening of prospective program beneficiaries, family SES indices were constructed for two largely middle-class undergraduate samples and a socioeconomically disadvantaged working-student sample from the Philippines. Indices were constructed for assets, housing and appliances, perceived financial difficulties, financially-draining life circumstances, and financing. Loadings resulting from nonlinear principal component analysis served as bases for reducing the indicators for an index. The resulting indices for the middle and lower social class samples largely differ in their indicators and underlying factor, reflecting the different extent and patterns of socioeconomic adversity. The indices for the middle class sample distinguish between objective indicators and perceived financial difficulties. The indices for the lower social class reflect a pervasive and multidimensional experience of socioeconomic adversity.